OPTIMIZING THE PARAMETERS OF THE GLASS FIBER IMPREGNATION PROCESS BY MEANS OF EXPERIMENT PLANNING METHOD - POSONSKIY, SERGIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The workpaper examines the structural features and selection of composite materials components, in particular the matrix and reinforcing elements, which together form a material with improved mechanical and operational properties. The classification of matrices by type (polymer, metal, ceramic) is described and the requirements for polymer resins most often used in the production of structural composites are given. Special attention is paid to the technology of filament winding, in particular the wet winding method, as the most common method of forming composite shafts from fiberglass and carbon fiber. Key factors affecting the quality of impregnation of reinforcing fibers with resin are identified, such as resin viscosity, fiber drawing speed, tension, bath geometry and properties of the resin system. It is emphasized that uniform and complete impregnation of fibers is critically important for ensuring the strength, stiffness and durability of the finished product.The paper presents the results of studying the process of impregnation of fiberglass tows with resins applying the software module “Design Analysis of Experiments”. Experiment planning methods were applied to determine the influence of the main technological parameters – winding speed, tow thickness and resin viscosity on the impregnation coefficient. A mathematical model and response surfaces were developed, which allow assessing the interaction of factors and establishing their optimal values. It was found that the maximum impregnation coefficient is achieved at a winding speed of 1136 RPM, a tow thickness of 81 micrometres, and a resin viscosity of 0.86 Pa·s. The results can be used to improve the efficiency of composite materials production processes.
Keywords: composite; matrix; resin; fiberglass tow; impregnation; experimental design; viscosity; winding speed; impregnation coefficient; response surface